Fathul Arifin by Shaykh Khatib Sambas: The Relevance of the Qadiriyah–Naqshabandiyah Sufi Path to Islamic Religious Education at the Junior Secondary School Level (SMP/MTs) - Zahid, Ahmad (Fakultas Tarbiyah Institut Agama Islam Ngawi, 2026)
This article seeks to conduct an in-depth reading of the book Fathul Arifin within the field of Sufism, particularly in relation to the Qadiriyah wa Naqshabandiyah Order. The Qadiriyah wa Naqshabandiyah Order has a noble objective, namely to cultivate the human soul so that it constantly remembers Allah through acts of dhikr and the practice of Allah’s commands contained within those remembrances. Likewise, the tarekat emphasizes continuous remembrance of Allah, both in movement and in stillness, so that a Sufi feels perpetually under the supervision of Allah SWT. Over time, the use of Fathul Arifin has experienced a decline in interest as a reference for worship and righteous deeds, due to the easy accessibility of instant literacy sources, especially through the internet and social media. This research aims to restore the aura of classical texts through an in-depth study of Fathul Arifin, integrated with the Islamic Religious Education (PAI) curriculum at the junior secondary school level (SMP/MTs), in order to identify points of relevance so that Fathul Arifin can be used as a reference for learning. The research method employed is library research using a textual criticism (textology) approach. Textology is a discipline that studies the content written within manuscripts. The manuscript examined in this study is Fathul Arifin by Shaykh Khatib Sambas. The results of this study indicate that there is relevance between the SMP/MTs PAI curriculum and the Qadiriyah wa Naqshabandiyah Order in a small portion of the PAI content. Although only a limited part is directly relevant between Fathul Arifin and the PAI curriculum, intersections and alignments can still be found in terms of intentions and objectives contained in both the SMP/MTs PAI curriculum and the book Fathul Arifin.